Sistem Informasi Manajemen Arsip Berbasis Website Pada Kantor Camat Danau Sipin - Shahfitri, Nurhafni; Siahaan, Kondar (Jurnal Manajemen Sistem Informasi, 2022)
The Danau Sipin Sub-District Office is a part of the Jambi City Government which is engaged in community service. Inside the Danau Sipin sub-district office consists of many fields including the field of Government, the field of Public Services, the field of Social Welfare, the field of Community Empowerment, the field of Security and Order, and the field of Finance. From all fields, there is no good archive management for each existing file. So that it often causes several problems including, frequent file loss, it is difficult to find old files if needed again, superiors find it difficult to make decisions if the decision must be based on files from the past period, files accumulate in the room causing the room to be cramped and messy, there is no management for borrowing archives from one field to another causes files to often be lost and separate. The purpose of this research is to analyze and design a Website-based Archive Management Information System at the Head Office of Danau Sipin for the problems that are being faced. Data collection was carried out by interviewing the district head and archive managers. In addition, the system development method used is a waterfall with UML (Unified Modeling Language) and Balsamiq Mockups to design a user interface. The output of this research is a design or prototype of a website-based archive management information system at the Head Office of Danau Sipin, Jambi City.